MULTIPLE CUTANEOUS PILOLEIOMYOMA WITH UTERINE FIBROIDS (REED’S SYNDROME): A RARE CASE REPORT - Roma N, Rajdeo; A C, Shrivastava; A V, Shrikhande (International Journal of Clinical and Biomedical Research, 2015)
Cutaneous leiomyomas comprise approximately 5% of all leiomyomas. Solitary occurrence is more common than generalized. Multiple cutaneous piloleiomyomas are rare, painful and difficult-to-treat benign tumors originating in the arrectores pilorum muscles of the hair follicles. Multiple Cutaneous piloleiomyomas are associated with uterine fibroids in women (Reed’s syndrome) and it is a marker of a condition called hereditary leiomyomatosis and renal cell cancer (HLRCC). We report a case of multiple cutaneous piloleiomyoma with uterine fibroid in an adult female. Because of its rarity and association with renal cell cancer, it deserves a mention in literature. KEYWORDS: Cutaneous leiomyoma; Uterine leiomyoma; Painful nodules.